Multigroup Analisis Penggunaan Aplikasi Pengiriman Makanan Saat Pandemik Covid-19 - Rifadli D. Kadir; Juniaty Ismail (Scimadly Publishing, 2022)
The impact of the Covid-19 pandemic has changed the order of human life, especially on consumer behavior. Consumer behavior that transforms from manual to digital in shopping, increasingly dominated by the choice of using food delivery and E-Payment applications. Therefore, this study aims to test the UTAUT-2 Theory against the use of food delivery apps, with SEM-PLS analysis tools and using the Multigroup Gender Use Analysis test on 134 respondents spread across Gorontalo Province. The results showed that Performance Expectancy, Price Value, and Habit influence Behavior intentions. Meanwhile, for Effort Expectancy, Social Influence, Facilitating Conditions, and Hedonic Motivation has no effect on behavior intentions using food delivery apps. In addition, multigroup analysis also showed that gender was not an influence on the use of food delivery apps during the covid-19 pandemic. This study has limitations only using the UTAUT2 model in predicting the behavior intention of food delivery applications during the covid-19 pandemic.